IMPLEMENTASI PEMBELAJARAN SAINTIFIK PADA PEMBELAJARAN FISIKA SMA TOPIK MATERI ELASTISITAS DAN HUKUM HOOKE - Maya Masita Admiyati Putri; Pendi Sinulingga; Theo Jhoni Hartanto (Vidya Karya, 2019)
Abstract. The purpose of this study was to describe the results of the implementation of scientific learning on the topic of elasticity and Hooke's law relating to: (1) students 'science process skills and (2) students' learning outcomes completeness. This study was a pre-experimental study using a one-shot case study design. The research subjects were the 24 students of class XI MIA-4 in one of the senior high schools in Palangka Raya City. Based on the results of data analysis, the completeness of student learning outcomes in the topic of elasticity and Hooke’s law by applying scientific learning obtained that: (1) students science process skills with very good criteria amounted to 33% of students, with good criteria amounted to 50% of students, and with sufficient criteria amounted to 17% of students and (2) students classical completeness was as big as 75%. Keywords: Science process skills, completeness of learning outcomes, scientific learning, physics Abstrak - Tujuan penelitian ini adalah untuk menggambarkan hasil implementasi pembelajaran saintifik pada topik elastisitas dan hukum Hooke yang berkaitan dengan: (1) keterampilan proses sains peserta didik dan (2) ketuntasan hasil belajar peserta didik. Penelitian ini merupakan sebuah studi pre-experimental menggunakan desain one-shot case study. Subyek penelitian adalah siswa kelas XI MIA-4 di salah satu SMA di Kota Palangka Raya dengan jumlah peserta didik 24 orang. Berdasarkan hasil analisis data, ketuntasan hasil belajar peserta didik pada topik elastisitas dan hukum Hooke dengan menerapkan pembelajaran saintifik diperoleh hasil: (1) Keterampilan proses sains peserta didik dengan kriteria sangat baik berjumlah 33%, kriteria baik 50% peserta didik, dan kriteria cukup baik 17% peserta didik. (2) ketuntasan klasikal peserta didik adalah sebesar 75%.. Kata Kunci: Keterampilan proses sains, ketuntasan hasil belajar, pembelajaran saintifik, fisika